Cloning, DNA sequence and in vitro transcription/translation analysis of a 3.2 kb EcoRI/HindIII fragment of Leuconostoc oenos bacteriophage L10 - Sutherland, Mark H.(Mark Hylton) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1994.